Simulation-based Analysis of a Dynamic Voltage Restorer under Different Voltage Sags with the Utilization of a PI Controller - Soomro, A. H.; Larik, A. S.; Mahar, M. A.; Sahito, A. A.; Sohu, I. A. (Engineering, Technology & Applied Science Research, 2020)
Power quality problems are becoming a major issue. Every utility company consumer desires to receive steady-state voltage, i.e. a sinusoidal waveform of constant frequency as generated at power stations, but the influence of disturbances in the shape of sags and swells, interruptions, transients and harmonic distortions which affect power quality, resulting in loss of data, damaged equipment, and augmented cost. The most powerful voltage disturbance is the sag voltage. In this paper, a Dynamic Voltage Restorer (DVR) is proposed for sag voltage compensation. It is cost-effective and protects critical loads in a good manner from balanced or unbalanced sag voltage. Control strategy (such as a PI controller) is adopted with DVR topology and the performance of such a device with the proposed controller is analyzed through simulation in MATLAB/Simulink. Three types of faults are utilized, which are available in MATLAB/Simulink pack, for obtaining the sag voltage. The specific range of total harmonic distortion percentage is also discussed. After the result validation of the DVR topology in MATLAB/Simulink, it has been seen that the proposed topology is able to compensate the sag voltage of any type of fault and reduce the unbalancing and voltage distortions of the grid.